Comparison of very affordable immersion pump and heart-lung-machine for post mortem CT angiography in forensic pathology – A case-control study. (September 2022) - Schweitzer, Wolf; Ebert, Lars; Thali, Michael J.
Highlights: Identification of an alternative pump design / principle (immersion centrifugal pump) and comparison with established historical de-facto standard (roller pump). Comparison using age-sex matched sample and quantitative aspects of vascular contrast filling. Better result of centrifugal pump may be explained technically, in that these pumps are designed for Newtonian fluids, whereas roller pumps usually have their specific role in fluids that are not routinely pumped during post mortem computed tomography angiography. Abstract: Full body post mortem CT angiography (PMCTA) in forensic medicine started on a larger scale with relatively expensive roller-pumps for what in essence seems to be a task consisting of pumping mostly homogenous contrast fluids. At considerably lower cost, centrifugal pumps are a technically powerful alternative. We compare a very affordable immersion pump (IP) with a heart lung machine (HLM) for an iodine based vascular contrast agent in a age-sex matched case-control study of 10 each. The IP outperformed the HLM, in part with statistical significance, depending on the aspect or metric that was compared. Concluding, the IP may be preferred as a useful and affordable alternative over a more expensive roller-pump.